The influence of indoor acoustical parameters on student perception in classrooms - Avsar, Yasar; Gonullu, M. Talha (INST NOISE CONTROL ENGINEERING, 2010)
This study presents the results of a field study carried out at high schools to determine the effects of both indoor and outdoor noise levels on educational quality. Two schools having the highest outdoor noise levels due to dense commercial facility and car traffic in Istanbul were selected for the study from among 67 schools. The noise survey studies were conducted in both occupied and unoccupied classrooms. Noise measurements were also conducted with the windows open and closed. A-weighted outdoor noise levels were between 74-80 dB (L(eq), for one hour in a day and five different time periods) at the facades of classrooms. Indoor noise levels varied between 60 and 63 dBA (L(eq), h/day) when the classrooms were occupied. Comparisons of measured and recommended levels are made. Degrees of annoyance and dissatisfaction obtained for the above comparisons are determined for the classrooms by a questionnaire to test the statistical meaning of the measured results. (C) 2010 Institute of Noise Control Engineering.
Keywords: Acoustics; Engineering